Method for producing ion exchange resin, ion exchange resin and use thereof

CN122999296APending Publication Date: 2026-10-30HUIZHOU YIWEI HYDROGEN ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611289790.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

上述制备方法工序繁琐、生产周期长、离子交换效率低,且存在生产安全隐患

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999296A_ABST
    Figure CN122999296A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of ion exchange resin, ion exchange resin and application thereof. The preparation method of the ion exchange resin provided by the application utilizes the synergistic effect of high-flash-point ethers and salt solution, combines the "resin precipitation washing" and "ion exchange" in the related art, exchanges the anions while the resin is precipitated, can effectively shorten the process flow, reduce the amount of organic reagent, improve the ion exchange efficiency, has high flexibility, and is suitable for large-scale industrial production of ion exchange resin of various anion types.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ion exchange resin preparation, specifically to methods for preparing ion exchange resins, ion exchange resins and their applications. Background Technology

[0002] Anion exchange membrane electrolyzers are widely used in water electrolysis, and the anion exchange membrane is one of the key components of this type of electrolyzer. Anion exchange membranes generally consist of a three-dimensional network framework formed by the polymer backbone of the resin and charged ion-conducting groups, which are covalently connected to the polymer backbone. In related technologies, the preparation of anion exchange resin typically involves precipitating the resin from its crude solution, washing it, and then soaking it in a salt solution for several to tens of hours to convert the resin into anionic form. This process requires a large amount of organic solvent and the salt solution needs to be changed multiple times during soaking. The above preparation method is cumbersome, has a long production cycle, low ion exchange efficiency, and poses production safety hazards. Summary of the Invention

[0003] Therefore, embodiments of this application provide a method for preparing ion exchange resins, ion exchange resins, and their applications. The method for preparing ion exchange resins provided in this application utilizes the synergistic effect of high flash point ethers and salt solutions to combine "resin precipitation and washing" with "ion exchange" in related technologies, enabling the exchange of anions to be completed simultaneously with resin precipitation. This effectively shortens the process flow, reduces the amount of organic reagents used, improves ion exchange efficiency, and offers high flexibility, making it suitable for large-scale industrial production of ion exchange resins with various anion types.

[0004] The first aspect of this application provides a method for preparing an ion exchange resin, comprising: A solution comprising a first solution and an alkaline resin, wherein the first solution comprises a salt solution and an ether; wherein the flash point of the ether is ≥60℃; the salt solution comprises a target anion; and the alkaline resin comprises a skeleton resin. Solid-liquid separation yields an ion exchange resin; the ion exchange resin comprises a resin and the target anion attached to the framework resin.

[0005] In some embodiments of this application, the volume ratio of the salt solution to the ether in the first solution is 1:(0.2-5).

[0006] In some embodiments of this application, the salt solution comprises salt, which accounts for 4%-20% of the mass of the salt solution.

[0007] In some embodiments of this application, the boiling point of the ether is 150 °C-250 °C.

[0008] In some embodiments of this application, the ether includes one or more of diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethylene glycol monobutyl ether, and dipropylene glycol methyl ether.

[0009] In some embodiments of this application, the salt solution comprises a salt, the salt comprising metal ions and the target anion, the target anion comprising OH-. - CO3² - Cl - ,Br - I - NO3 - HCO3 - One or more of the following, wherein the metal ions include Na + and / or K + .

[0010] In some embodiments of this application, the solvent for the salt solution is water.

[0011] In some embodiments of this application, the mixing of the first solution and the alkaline resin solution includes: adding the first solution to the alkaline resin solution while stirring to obtain a mixture; the stirring speed is 50 rpm-65 rpm.

[0012] In some embodiments of this application, after mixing the first solution and the alkaline resin solution, and before solid-liquid separation, the mixture is further further comprising: stirring the mixture of the alkaline resin solution and the first solution at a rate of 50 rpm to 65 rpm for 0.5 h to 2 h.

[0013] In some embodiments of this application, the mass percentage of the alkaline resin is 11%-30% based on the total mass of the alkaline resin solution.

[0014] In some embodiments of this application, the alkaline resin includes a quaternized alkaline resin, and the skeletal resin of the quaternized alkaline resin includes one or more of a fluorocarbon skeletal resin, an ether-containing skeletal resin, and a polyaromatic ring skeletal resin.

[0015] In some embodiments of this application, the solvent in the solution of the alkaline resin includes one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetonitrile.

[0016] The second aspect of this application provides an ion exchange resin, which is prepared using the preparation method of the ion exchange resin provided in the first aspect of this application.

[0017] A third aspect of this application provides an ion exchange membrane, including the ion exchange resin provided in the second aspect of this application.

[0018] The fourth aspect of this application provides an ion exchange membrane electrolyzer, including the ion exchange membrane provided in the third aspect of this application. Attached Figure Description

[0019] Figure 1 Comparison charts of single-cell polarization performance of Examples 1-2, Examples 7-8, Example 14, and Comparative Example 1 of this application; Figure 2 This is a comparison chart of the single-cell stability of Examples 1, 14 and Comparative Example 1 of this application. Detailed Implementation

[0020] Anion exchange membrane electrolyzers are widely used in water electrolysis, and the anion exchange membrane is one of the key components of this type of electrolyzer. Anion exchange membranes generally consist of a three-dimensional network framework formed by the polymer backbone of the resin and charged ion-conducting groups, which are covalently connected to the polymer backbone. In related technologies, the preparation of anion exchange resin generally involves first precipitating the resin from its crude solution, washing it, and then soaking it in a target salt solution for 6-24 hours to convert the resin into the target anion form. This resin precipitation process typically requires the use of large amounts of organic solvents, such as ethanol, ethyl acetate, acetone, and diethyl ether, posing a high risk of fire and explosion and involving controlled chemicals. Furthermore, the stirring and soaking process is not only time-consuming but also requires frequent replacement with fresh target salt solution, necessitating repeated solid-liquid separation operations, making the process cumbersome. Furthermore, due to the diffusion resistance within the resin's internal pores, ion exchange is often incomplete in the above process, with ion conversion rates typically not exceeding 85%. Residual anions can affect the application of the ion exchange resin. Additionally, some target salt solutions have a strong swelling effect on the resin, and prolonged immersion may damage the resin's pore structure. Moreover, in related technologies, the ion-exchanged resin requires extensive washing with deionized water to remove excess salt, generating large amounts of saline wastewater and increasing wastewater treatment costs.

[0021] To address the aforementioned technical problems, this application provides a method for preparing an ion exchange resin, comprising: S1. A solution containing a first solution and an alkaline resin, wherein the first solution comprises a salt solution and an ether; wherein the flash point of the ether is ≥60℃; the salt solution comprises a target anion, and the alkaline resin comprises a framework resin. It is understood that the salt solution comprises a salt, which contains the target anion, and the salt is used to provide the target anion for resin exchange; the alkaline resin is used to provide the framework resin, and the alkaline resin comprises the framework resin and exchangeable anions attached to the framework resin.

[0022] S2. Solid-liquid separation yields ion exchange resin; the ion exchange resin includes a framework resin and target anions attached to the framework resin.

[0023] In this embodiment, the solution of the basic resin can be, for example, a crude solution of basic resin obtained during the preparation process of the basic resin. The crude solution of basic resin may include, for example, basic resin, unreacted monomers, reaction byproducts, and solvent. Basic resin comprises a three-dimensional network structure formed by a backbone resin and exchangeable anions, and generally has a rich porous structure.

[0024] The rapid and efficient method for preparing ion exchange resins established in this application embodiment can directly process crude alkaline resin solution in one step, simultaneously completing ion exchange and resin precipitation within a short time (e.g., 0.5 h-2 h). This significantly shortens the preparation cycle of ion exchange resins with different ion types, facilitating the research and development and preparation of electrolytic cells with various properties. Specifically, compared to traditional processes, the production cycle of ion exchange resins prepared by the method in this application embodiment can be shortened by 30%-50%, and the amount of organic solvent used can be reduced by 40%-60%.

[0025] In step S1, the low-volatility ether in the first solution allows sufficient time for the solution to penetrate deep into the pore structure of the basic resin, achieving deep penetration and complete dissolution of stubborn impurities. This results in a high removal rate of impurities (such as raw materials and byproducts remaining on the framework resin during basic resin preparation). Simultaneously, the target anions in the first solution replace the exchangeable anions attached to the framework resin, forming an ion exchange resin. Therefore, this preparation method effectively improves the ion exchange conversion rate and has high versatility, enabling the preparation of ion exchange resins with various anion types. Furthermore, the first solution is miscible with the basic resin solution, inducing the ion exchange resin to precipitate out as a precipitate, which is then separated into solid and liquid components in step S2 to obtain the final ion exchange resin.

[0026] Furthermore, ion exchange resins are generally required to be prepared into ion exchange membranes for application. During the fabrication of ion exchange membranes, the ethers exhibiting the aforementioned characteristics have suitable volatilization rates, which facilitate the controlled self-assembly of the polymer chains in the backbone resin, forming a dense membrane layer with low stress and continuous ion channels. This effectively reduces the membrane resistance of the ion exchange resin and improves its thermal stability.

[0027] Furthermore, the low volatility of ethers can eliminate the risk of fire and explosion in the manufacturing process of related technologies from the source, and the ethers used in this application can be non-regulated chemicals.

[0028] In some embodiments of this application, the salt solution comprises salt and water, wherein the salt includes metal ions and a target anion. The target anion includes OH-. -CO3² - Cl - ,Br - I - NO3 - HCO3 - One or more of the following, including metal ions such as Na + and / or K + Correspondingly, the ionic form of the prepared ion exchange resin can include OH. - CO3² - Cl - ,Br - I - NO3 - HCO3 - One or more of these. Those skilled in the art can select the specific type of salt based on the ion exchange resin containing the target anion type.

[0029] In some embodiments of this application, the volume ratio of salt solution to ether in the first solution is 1:(0.2-5). This facilitates the balance between salting-out precipitation and ion exchange in the system, promotes the complete precipitation of the ion exchange resin, and enhances the driving force of ion exchange. Simultaneously, it allows the ether in the first solution to effectively perform its "pre-regulation" function, such as moderately swelling the framework resin, reducing the interfacial tension between the first solution and the framework resin, and optimizing the structural orientation of the framework resin in subsequent ion exchange membrane fabrication processes to improve the performance of the final ion exchange membrane. Furthermore, since the salt solution is an aqueous solution of salt, controlling the volume ratio within the aforementioned range also helps ensure the uniformity and stability of the two-phase system, avoiding phase separation of the mixture (the solution of the first solution and the basic resin). The resulting ion exchange resin has less salt residue, is easier to remove, and exhibits superior solubility and film-forming properties. Specifically, the volume ratio of salt solution to ether can be, for example, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.2, 1:4.5, 1:4.8, 1:5, etc.

[0030] In some specific embodiments, the volume ratio of salt solution to ether in the first solution is 1:(0.5-2). This facilitates the simultaneous enhancement of ion exchange and precipitation of ion exchange resin, thereby further improving the yield and ion exchange efficiency of the ion exchange resin; for example, the yield of ion exchange resin ≥95% and the ion exchange efficiency ≥95% can be achieved within 1-3 hours. Furthermore, controlling the volumes of both within this range provides a stronger "pre-regulation" effect for the ion exchange resin, which is more conducive to the formation of a more stable and continuous ion channel structure in the ion exchange resin and its membrane, while reducing the risk of crystallization damage caused by salt residue and improving the long-term stability of the ion exchange membrane. Moreover, it also facilitates large-scale industrial production and reduces material costs.

[0031] In some embodiments of this application, the salt content is 4%-20% based on the mass of the salt solution. This serves two purposes: first, it reduces the risk of salt supersaturation and precipitation, and also reduces the risk of damage to the pore structure of the framework resin due to excessively high osmotic pressure; second, it enhances the driving force for ion exchange in the system and promotes the precipitation of the ion exchange resin. Specifically, the salt content can be, for example, 4%, 5%, 8%, 10%, 12%, 15%, 18%, or 20% based on the mass of the salt solution.

[0032] In some specific implementations, the salt concentration is 5%-15% of the total salt content, based on the mass of the salt solution. This reduces competitive migration interference between ions, ensuring the selectivity of the ion exchange reaction. Simultaneously, a moderate salt concentration controls the degree of resin swelling, preventing impact on the structure of the framework resin, thereby reducing the surface roughness of the final ion exchange membrane and improving its smoothness and density. Furthermore, a suitable salt concentration also reduces the burden on subsequent water washing and desalination, optimizing the overall production cost of the ion exchange resin.

[0033] In some embodiments of this application, the boiling point of the ether is ≥150 °C. While controlling the flash point of the ether to ≥60 °C, further controlling the boiling point to ≥150 °C is more conducive to suppressing ether volatilization, and more conducive to ensuring that the first solution has sufficient time to penetrate deep into the pore structure of the alkaline resin, achieving deep penetration and complete dissolution of stubborn impurities, and further preventing fires from occurring during the preparation process at the source.

[0034] In some specific embodiments of this application, the boiling point of the ether is 150 ℃-250 ℃. Further controlling the boiling point of the ether to ≤250 ℃ allows the reagent to be recovered and reused using conventional vacuum distillation in subsequent waste liquid treatment and solvent recovery processes. This results in a moderate recovery temperature and controllable energy consumption, which is beneficial for cost control in industrial production. Simultaneously, ethers within the aforementioned boiling point range have good compatibility with the skeletal resin, preventing loss of pre-regulation capabilities due to excessively rapid evaporation during washing, and avoiding significantly increased difficulty in waste liquid treatment due to excessively high boiling points. Specifically, the boiling point of the ether in the embodiments of this application can be, for example, 150 ℃, 160 ℃, 170 ℃, 180 ℃, 190 ℃, 200 ℃, 210 ℃, 220 ℃, 230 ℃, 240 ℃, 250 ℃, etc.

[0035] In some embodiments of this application, the ether in the first solution includes, but is not limited to, one or more of diethylene glycol monobutyl ether (DGBE), diethylene glycol dimethyl ether (DEGDME), ethylene glycol monobutyl ether (EGBE), and dipropylene glycol methyl ether (DPM). These reagents have suitable flash points and boiling points, possess strong impurity removal capabilities, and when combined with salt solutions and alkaline resin solutions, they can form systems more conducive to ion exchange and resin precipitation, thus improving ion exchange efficiency and ion exchange resin yield. Furthermore, the molecules of these various ethers readily adsorb at the interface between the framework resin and the solution, inducing the framework resin to pre-align, resulting in an ordered conformation between the hydrophilic and hydrophobic segments. This ordered conformation is "remembered" by the framework resin after the ether solvent is removed. When the ion exchange resin is subsequently redissolved in dimethyl sulfoxide (DMSO) to prepare an ion exchange membrane, the pre-arranged segments can further self-assemble along the existing orientation, eventually forming a continuous and interconnected hydrophilic ion channel. Combined with the moderate evaporation rate of this type of ether, the ion exchange resin shrinks uniformly during the drying process, avoiding internal stress concentration, thereby obtaining a dense, uniform, and low-defect membrane structure, providing a structural basis for reducing the resistance of the ion exchange membrane and improving its long-term operational stability.

[0036] In some embodiments of this application, the mass percentage of the alkaline resin in the solution is 11%-30%, based on the total mass of the alkaline resin solution. In some specific embodiments, the alkaline resin accounts for 15%-20% of the mass of the alkaline resin solution. This facilitates the precipitation of the ion exchange resin. In the embodiments of this application, the mass percentage of the alkaline resin in the alkaline resin solution can be, for example, 11%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, etc.

[0037] In some embodiments of this application, the solvent for the alkaline resin solution is selected from one or more of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), and acetonitrile. These solvents can be used as solvents in the alkaline resin synthesis process and have good compatibility with the first solution, which is beneficial for the preparation of ion exchange resins.

[0038] In some embodiments of this application, the alkaline resin includes a quaternized alkaline resin, and the skeletal resin of the quaternized alkaline resin includes, but is not limited to, one or more of fluorocarbon skeletal resins, ether-containing skeletal resins, and polyaryl ring skeletal resins. In some specific embodiments of this application, the skeletal resin of the quaternized alkaline resin includes, but is not limited to, one or more of perfluorosulfonic acid polymers, perfluoroquaternary ammonium polymers, polyphenylene ether, polyetheretherketone, polyethersulfone, polyarylpiperidine, polyarylpyridine, polystyrene, polyphenylene sulfide, polyethylene, polypropylene, and polyvinyl chloride. In some specific embodiments, the alkaline resin includes one or more of polyarylpiperidine quaternary ammonium type resins, polyetherketone quaternary ammonium type resins, or perfluoro skeletal quaternary ammonium type resins.

[0039] In some embodiments of this application, the alkaline resin is obtained by quaternization modification of the above-mentioned skeleton resin. The quaternization reagent used for quaternization modification may be, but is not limited to, one or more of iodomethane, bromomethane, bromoethane, bromopropane, bromobutane, bromododecane, chloromethane, chloroethane, chloropropane, benzyl chloride, benzyl bromide, dimethyl sulfate, and diethyl sulfate.

[0040] In some embodiments of this application, step S1, mixing the first solution and the alkaline resin solution, includes: adding the first solution to the alkaline resin solution while stirring to obtain a mixture. In some embodiments, the stirring rate is 50 rpm-65 rpm. In some specific embodiments, mixing the first solution and the alkaline resin solution includes: adding the first solution dropwise to the alkaline resin solution while stirring to obtain a mixture. This facilitates obtaining a more homogeneous system, which is beneficial for subsequent ion exchange and resin precipitation. Specifically, during the mixing process in step S1, the stirring rate can be, for example, 50 rpm, 52 rpm, 55 rpm, 58 rpm, 60 rpm, 62 rpm, or 65 rpm.

[0041] To achieve more complete ion exchange and improve the yield of ion exchange resin, some embodiments of this application further include, after mixing the first solution and the basic resin solution and before solid-liquid separation, stirring the mixture of the basic resin solution and the first solution at a rate of 50 rpm to 65 rpm for 0.5 h to 2 h. Specifically, the stirring rate can be, for example, 50 rpm, 52 rpm, 55 rpm, 58 rpm, 60 rpm, 62 rpm, or 65 rpm, and the stirring duration can be, for example, 0.5 h, 1 h, 1.5 h, or 2 h. In some specific embodiments, the stirring duration is 1 h. This balances time cost with higher yield and ion exchange efficiency.

[0042] In some embodiments of this application, step S2, after solid-liquid separation, further includes washing the obtained solid once or multiple times. Washing can be done using, for example, deionized water or a solution of the same salt. Washing can remove residual solvent and excess salt from the surface of the ion exchange resin. The specific solid-liquid separation process can be centrifugation. Specifically, the product obtained in step S1 is centrifuged at 50 rpm for 20 min, the supernatant is discarded, and the solid is obtained. Deionized water is added to the solid, and the mixture is stirred and washed for 5 min, then centrifuged at 50 rpm for 20 min, and the supernatant is discarded. This washing is repeated twice to obtain the ion exchange resin. It is understood that washing also includes drying, which can be vacuum drying for 24 h at a vacuum level of -0.095 MPa.

[0043] In this embodiment, the anion type of the ion exchange resin can be determined by ion chromatography.

[0044] This application also provides an ion exchange resin, which is prepared using the ion exchange resin preparation method described above in this application.

[0045] Because the preparation method provided in this application is highly flexible, in this application embodiment, the ion exchange resin is, for example, but not limited to, OH. - Type, CO3² - Type, Cl - Type, Br - Type, I - Type, NO3 - Type, HCO3 - Type. OH - Type Ion exchange resins have the highest ionic conductivity; HCO3 - / CO3² - Type II ion exchange resins have better stability but lower conductivity; Cl - ,Br - I -Halogenated ion exchange resins have different hydrophilicity and ion transport properties. Those skilled in the art can choose flexibly according to actual needs.

[0046] This application also provides an ion exchange membrane, including the aforementioned ion exchange resin. This ion exchange membrane can be used in anion exchange membrane (AEM) electrolyzers.

[0047] In some embodiments of this application, the ion exchange resin can be dissolved in a solvent to obtain an ion exchange resin solution, which is then subjected to membrane fabrication using a process commonly used in the art to obtain an ion exchange membrane. Specifically, the solvent can be any solvent known in the art suitable for dissolving ion exchange resins, such as, but not limited to, dimethyl sulfoxide (DMSO).

[0048] This application also provides an electrolyzer including the aforementioned ion exchange membrane. Specifically, the electrolyzer further includes other accessories, which may be accessories well-known to those skilled in the art and applicable to AME electrolyzers.

[0049] The technical solution of this application will be described in detail below with reference to several embodiments.

[0050] Solution for preparing basic resin 150.0 g of polyarylpiperidine resin, 750.0 mL of dimethyl sulfoxide (DMSO), and 100.0 g of iodomethane were added to a three-necked flask. The mixture was stirred at 80 °C and 150 rpm for 15 hours to obtain a crude solution of quaternized polyarylpiperidine basic resin. The initial anionic form of the resin was I. - type.

[0051] Preparation of the first solution Weigh the salts corresponding to each example according to the parameters in Table 1, add an appropriate amount of deionized water, and then make up to volume in a volumetric flask to obtain the salt solutions of Examples 1 to 7. Each salt solution from each embodiment was mixed with an equal volume of ether (volume ratio 1:1) and stirred until homogeneous to obtain the first solutions of Examples 1 to 7.

[0052] Preparation of ion exchange resins (1) The crude quaternized polyarylpiperidine resin solution was transferred to a reaction vessel, and 2000 mL of the first solution was slowly added dropwise over a stirring period of 150 rpm. During the addition, the resin gradually precipitated from the mixed solution in solid form. After the addition was completed, stirring was continued according to the exchange time in Table 1 to ensure that the ion exchange was fully carried out, and a mixture was obtained.

[0053] (2) Solid-liquid separation and washing Centrifuge the mixture at 50 rpm for 20 minutes and discard the supernatant. Add 1000.0 mL of deionized water to the precipitate, stir and wash for 5 minutes, then centrifuge again at 50 rpm for 20 minutes and discard the supernatant. Repeat the washing process twice.

[0054] The washed resin was transferred to a petri dish and placed in an 80 °C vacuum drying oven, where it was dried for 24 hours under a vacuum of -0.095 MPa to obtain the ion exchange resins of the target ion type for each embodiment. The ion exchange capacity (IEC) of each embodiment is also summarized in Table 1.

[0055] Table 1

[0056] The results of Examples 1 to 7 show that the preparation method of ion exchange resin provided by the present invention can convert quaternized polyarylene piperidine resin from I to 2 liters within 1-2 hours. - By converting the ion type to the target anion type, a high ion exchange capacity can be achieved, with an exchange efficiency exceeding 93%. Compared with Comparative Example 1, this method significantly shortens the exchange time, simplifies the operation process, and enables the efficient preparation of exchange resins with different ion types.

[0057] Examples 8-11 The difference from Example 1 is that only the mass percentage of KOH in the salt solution was changed, and the exchange time of each example was fine-tuned. The parameters are summarized in Table 2. The IEC, ion exchange efficiency, and resin yield of Examples 8 to 11 are also summarized in Table 2.

[0058] Table 2

[0059] As can be seen from the data in Table 2, when the concentration of the salt solution is further controlled within the preferred range (5%-15%), both the ion exchange capacity and ion exchange efficiency are relatively high. It should be noted that when the salt solution concentration is 20%, although the ion exchange efficiency remains high, the increased concentration of the system leads to a significant increase in viscosity, and the homogeneity of the mixing between the salt aqueous solution and the ether solvent decreases, resulting in operational inconvenience.

[0060] Examples 12-15 The difference from Example 1 is that only the volume ratio of salt solution to ether was changed and the exchange time was finely adjusted. All parameters are summarized in Table 3. The IEC, ion exchange efficiency, resin yield and resin precipitation of Examples 12 to 15 and Example 1 are also summarized in Table 3.

[0061] Table 3

[0062] As can be seen from the data in Table 3, when the volume ratio of salt solution to ether in the first solution is controlled within the preferred range (1:2 to 2:1), the ion exchange efficiency and resin yield are both high, especially the resin precipitation, which is more conducive to actual production.

[0063] In the embodiments of this application, ion chromatography is used to determine the target anion and residual I in the resin before and after purification. - The specific steps are as follows: Weigh approximately 0.1 g of the dried resin membrane, cut it into small pieces, and place it in 20 mL of 1 mol / L NaNO3 solution. Shake for 24 h to allow the anions on the resin to be completely exchanged into the solution. Filter the exchange solution through a 0.22 μm filter membrane and determine the concentration using an ion chromatograph (equipped with a suppressed conductivity detector and an anion separation column). Calculate the concentration of each anion based on the standard curve, and calculate the ion exchange capacity (IEC) using the following formula: IEC (mmol / g) = C × V / m; where C is the concentration of the target anion in the exchange medium (mmol / mL), V is the volume of the exchange medium (mL), and m is the mass of the dry film (g).

[0064] Ion exchange efficiency = (IEC exp / IEC theo )×100%, of which, IEC exp To measure ion exchange capacity, IEC theo This represents the theoretical ion exchange capacity.

[0065] Set the following ratio Comparative Example 1 (1) Take 750 mL of the above-mentioned crude quaternized polyarylpiperidine basic resin solution, and slowly add 2 L of ethyl acetate while stirring (150 rpm). The resin gradually precipitates. Continue stirring for 30 minutes, then centrifuge at 50 rpm for 20 minutes and discard the supernatant. Add 2 L of ethyl acetate (flash point -4℃) to the precipitate, stir and wash for 1 hour, then centrifuge again at 50 rpm for 20 minutes and discard the supernatant. Repeat the ethyl acetate washing twice.

[0066] (2) Static ion exchange (45 °C, KOH solution replaced 3 times) The washed resin was transferred to a 5L reactor, and 2000.0 mL of 1.0 mol / L KOH aqueous solution (approximately 5.4% by mass) was added. The temperature was raised to 45°C, and the mixture was immersed and exchanged for 6 hours with stirring (150 rpm). Stirring was stopped, and the mixture was centrifuged at 50 rpm for 20 minutes, discarding the supernatant. Another 2000.0 mL of fresh 1.0 mol / L KOH aqueous solution was added, and the mixture was immersed and exchanged again at 45°C for 6 hours. This process was repeated, with the KOH solution replaced a total of 3 times, for a total exchange time of 18 hours.

[0067] (3) Washing and drying Centrifuge the ion-exchange mixture at 50 rpm for 20 minutes and discard the supernatant. Add 2 L of deionized water to the precipitate, stir and wash for 5 minutes, then centrifuge at 50 rpm for 20 minutes and discard the supernatant. Repeat the washing process three times. Transfer the washed resin to a petri dish and place it in an 80℃ vacuum drying oven. Dry under a vacuum of -0.095 MPa for 24 hours to obtain OH. - Type of polyarylpiperidine basic resin film.

[0068] (4) Ion type confirmation The OH content of the ion exchange resin in Comparative Example 1 was determined by ion chromatography. - The content was 2.25 mmol / g, and the exchange efficiency was approximately 84.9%. - The residue is approximately 0.25 mmol / g.

[0069] Comparative Example 2 The only difference from Example 1 is that the ether in the first solution is replaced with diethyl ether (flash point -45°C, boiling point 34.6°C).

[0070] In the preparation process of Comparative Example 2, after mixing the first solution and the alkaline resin solution, the system could not form a thermodynamically stable homogeneous system, exhibiting a three-phase coexistence of oil, water, and organic solvent. Furthermore, during the stirring and precipitation process, the system was a stable emulsion. During solid-liquid separation, the resin solid and emulsion were mixed, resulting in a high water content in the filter cake, a resin yield of less than 65%, and a large number of emulsion droplets entrained in the resin, leading to low product purity. In addition, due to the low flash point of diethyl ether, a large amount volatilized during stirring at room temperature, causing a rapid increase in the concentration of diethyl ether in the workshop air. This not only resulted in material loss (ether recovery rate less than 60%) but also posed a serious fire and explosion hazard.

[0071] The results of comparing the examples and the comparative examples show that the preparation method of the ion exchange resin provided in this application is highly efficient and safe.

[0072] Preparation of ion exchange membranes Take 2g of the ion exchange resins prepared in Examples 1-15 and Comparative Example 1, and add them to 10mL of dimethyl sulfoxide. Stir at 80°C until completely dissolved and homogeneous to obtain a resin slurry. Cut a PET base film of appropriate size and fix it on a horizontal platform. Coat 10mL of the resin slurry evenly on the preparation device and sweep it across at a uniform speed of 150mm / s to form a wet film with a thickness of 230μm. Place the coated wet film in a drying oven at 70°C for 10 hours to allow the solvent to evaporate completely, and obtain an ion exchange membrane. Finally, peel the dried membrane material off the base film for later use.

[0073] Single-pool performance test The anion exchange membranes prepared in the above embodiments and comparative examples were cut into 10cm × 10cm sizes. Anode catalyst layer slurry (a NiFe-LDH (layered double metal hydroxide) catalyst and ion-conducting resin dispersed in isopropanol) and cathode catalyst layer slurry (a Pt / Ru / C catalyst and ion-conducting resin dispersed in isopropanol) were prepared separately and uniformly coated on both sides of the anion exchange membrane using a spraying method. The anode catalyst loading was 1 mg / cm³. 2 Cathode catalyst loading 1 mg / cm 2 After being vacuum dried at 60℃, it is assembled with the anode gas diffusion layer (nickel foam and the cathode gas diffusion layer (carbon paper)) to form a film electrode. Then, it is cut to the required size and placed in an effective area of ​​5cm². 2 In the single-cell fixture, platinum-plated titanium plates are used as electrodes, a serpentine flow field design is employed, and polytetrafluoroethylene (PTFE) is used for sealing. During testing, a 1 mol / L KOH solution is used as the electrolyte, the flow rate is 100 mL / min, the temperature is 70℃, and after equilibration for 30 min, polarization curves are measured using constant current mode. Steady-state voltages at different current densities are recorded, and long-term stability tests (1 A / cm²) are also conducted. 2 (After running for 473 hours) the cell pressure decay rate was calculated to evaluate the single-cell performance of the anion exchange membrane.

[0074] Figure 1 This is a comparison chart of the single-cell polarization performance of Examples 1-2, Examples 7-8, Example 14, and Comparative Example 1 of this application. Figure 1 As can be seen, the current density (horizontal axis) is 1 A / cm². 2 At that time, the tank voltage of Example 1 was 1.647V, the tank voltage of Example 2 was 1.653V, the tank voltage of Example 7 was 1.651V, the tank voltage of Example 8 was 1.737V, the tank voltage of Example 14 was 1.677V, and the tank voltage of Comparative Example 1 was 1.727V. Compared with Comparative Example 1 and Example 8, Examples 1, 2, 7, and 14 showed lower operating tank voltages.

[0075] The fundamental reason why Examples 1, 2, 7, and 14 exhibited lower operating cell pressure is as follows: First, the salt concentration was controlled within the preferred range of 5% to 15%, ensuring sufficient ion exchange, with an IEC of 2.55-2.65 mmol / g and a high density of active sites; second, the ion exchange efficiency was high (≥96.2%). - Low residue (≤0.05mmol / g), avoiding residual I -The membrane material exhibits several advantages: firstly, it occupies active sites and blocks pores; secondly, high-flash-point ether solvents effectively remove organic impurities during washing, ensuring the purity of the membrane material. In contrast, Comparative Example 1 suffers from low IEC (2.25 mmol / g), insufficient exchange (84.9%), and low I... - High residue (0.25 mmol / g) resulted in a high cell pressure (1.727 V).

[0076] Figure 2 This is a comparison chart of single-cell stability of Embodiment 1, Embodiment 14, and Comparative Example 1 of this application, wherein the aforementioned... Figure 1 The horizontal axis is 1A / cm 2 The initial cell pressure is the cell pressure at the specified time. The final cell pressure is the cell pressure after 575 hours of operation in a single cell. The cell pressure decay rate is calculated according to "cell pressure decay rate = (final cell pressure - initial cell pressure) / time". The cell pressure decay rate refers to the rate at which the cell pressure of a single electrolytic cell increases over time under constant operating conditions. A higher cell pressure decay rate indicates a faster aging rate of the single cell. Figure 2 It can be seen that: the initial cell voltage of Example 1 was 1.651V, the final cell voltage was 1.816V, and the cell voltage decay rate was 0.294mV / h; the initial cell voltage of Example 14 was 1.651V, the final cell voltage was 1.838V, and the cell voltage decay rate was 0.325mV / h; the initial cell voltage of Comparative Example 1 was 1.727V, the final cell voltage was 1.986V, and the cell voltage decay rate was 0.433mV / h. Based on the above long-term stability test results, the cell voltage decay rates of Examples 1 and 14 are lower than those of Comparative Example 1, indicating that the ion exchange membranes prepared in this application have superior long-term operational stability. The reason why Comparative Example 1 has the highest decay rate (0.433mV / h) is that the traditional process leads to... - High residual level (0.25 mmol / g), during operation I - Slow release / migration leads to electrode contamination and ion channel blockage; residual organic impurities cause membrane / electrode contamination; high internal stress in the membrane structure leads to structural relaxation during long-term operation.

[0077] The above description is an exemplary embodiment of this application. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principles of this application, and these improvements and modifications are also considered to be within the scope of protection of this application.

Claims

1. A method for preparing an ion exchange resin, characterized in that, include: A solution comprising a first solution and an alkaline resin, wherein the first solution comprises a salt solution and an ether; wherein the flash point of the ether is ≥60℃; the salt solution comprises a target anion; and the alkaline resin comprises a skeleton resin. Solid-liquid separation yields an ion exchange resin; the ion exchange resin comprises a resin and the target anion attached to the framework resin.

2. The preparation method according to claim 1, characterized in that, In the first solution, the volume ratio of the salt solution to the ether is 1:(0.2-5).

3. The preparation method according to claim 1 or 2, characterized in that, The salt solution comprises salt, which accounts for 4%-20% of the mass of the salt solution.

4. The preparation method according to any one of claims 1-3, characterized in that, The boiling point of the ether is 150 ℃-250 ℃.

5. The preparation method according to any one of claims 1-4, characterized in that, The ether comprises one or more of diethylene glycol monobutyl ether, diethylene glycol dimethyl ether, ethylene glycol monobutyl ether, and dipropylene glycol methyl ether; and / or, The salt solution comprises a salt, the salt comprising metal ions and the target anion, the target anion comprising OH-. - CO3² - Cl - ,Br - I - NO3 - HCO3 - One or more of the following, wherein the metal ions include Na + and / or K + ; and / or, The solvent for the salt solution is water.

6. The preparation method according to any one of claims 1-5, characterized in that, The mixture of the first solution and the alkaline resin solution comprises: adding the first solution to the alkaline resin solution while stirring to obtain a mixture; the stirring speed is 50 rpm-65 rpm.

7. The preparation method according to any one of claims 1-6, characterized in that, After mixing the first solution and the alkaline resin solution, and before solid-liquid separation, the mixture is further further subjected to stirring at a rate of 50 rpm to 65 rpm for 0.5 h to 2 h.

8. The preparation method according to any one of claims 1-7, characterized in that, The alkaline resin includes a quaternized alkaline resin, and the backbone resin of the quaternized alkaline resin includes one or more of fluorocarbon backbone resins, ether-containing backbone resins, and polyaryl ring backbone resins; and / or, The solvent in the solution of the alkaline resin includes one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and acetonitrile.

9. An ion exchange resin, characterized in that, The ion exchange resin is prepared by the preparation method described in any one of claims 1-8.

10. An ion exchange membrane, characterized in that, Includes the ion exchange resin as described in claim 9.

11. An ion exchange membrane electrolyzer, characterized in that, Includes the ion exchange membrane as described in claim 10.